Pengaruh Brand Ambassador Carlos Sainz dan Product Quality terhadap Purchase Intention Produk L’oréal Paris melalui Brand Image pada Penggemar Formula 1 Indonesia - Amanda, Riska; Dwiridotjahjono, Jojok (Jurnal Simki Economic, 2026)
This study focuses on analyzing the role of Brand Ambassadors and Product Quality in influencing Purchase Intention for L'Oréal Paris products, with Brand Image as an intermediary variable among Formula 1 fans in Indonesia. The research uses an explanatory quantitative approach through a survey, with purposive selection of respondents and data collection using an online questionnaire. The data obtained was then analyzed using the PLS-SEM method through the SmartPLS version 4.0.9.9 application. The analysis results show that Brand Ambassador and Product Quality play a significant role in shaping Brand Image and increasing Purchase Intention. Brand Image is also proven to have a direct influence on Purchase Intention and functions as a partial mediator in the relationship between Brand Ambassador and Product Quality on purchase intention. The coefficient of determination value shows that more than 58% of the variation in Purchase Intention can be explained by the research model, with Product Quality as the variable that contributes the most. These findings indicate that the right brand ambassador selection strategy, accompanied by good product quality, can strengthen brand image and encourage increased consumer purchase intention. This study contributes by presenting a new perspective on the effectiveness of cross-industry marketing strategies, namely the use of motorsport athletes as brand ambassadors in the beauty industry, and explains the role of brand image as an important mechanism in increasing purchasing interest among Formula 1 fans in Indonesia.